2012
DOI: 10.1007/s10531-011-0210-1
|View full text |Cite
|
Sign up to set email alerts
|

Biodiversity and habitat mapping of Menorca Channel (western Mediterranean): implications for conservation

Abstract: Menorca Channel (Balearic Islands, western Mediterranean) comprises 98,700 Ha of continental shelf. It has been proposed to include this area in the Natura 2000 network due to the wide range of species and habitats of high conservation value found here, such as Posidonia oceanica meadows and maërl and coralligenous beds. This study aimed to establish a scientific basis for managing and protecting the continental shelf bottoms in Menorca Channel. Sampling was carried out with side-scan sonar, beam trawls, box c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
64
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(66 citation statements)
references
References 96 publications
(102 reference statements)
1
64
0
1
Order By: Relevance
“…see Dieuzede, 1940;Huvé, 1956;Costa, 1960;Bourcier, 1968;Blunden et al, 1977;Bordehore et al, 2003;Peña, 2010) and beam trawls (Barberá et al, 2012;Ellis et al, 2013). Images obtained by ROV, together with previous results (Joher et al, 2012), showed that the community dominated by S. fruticulosus was very homogeneous, and composed mainly of small maërl-forming species (S. fruticulosus and Phymatolithon calcareum).…”
Section: Methodsmentioning
confidence: 82%
See 2 more Smart Citations
“…see Dieuzede, 1940;Huvé, 1956;Costa, 1960;Bourcier, 1968;Blunden et al, 1977;Bordehore et al, 2003;Peña, 2010) and beam trawls (Barberá et al, 2012;Ellis et al, 2013). Images obtained by ROV, together with previous results (Joher et al, 2012), showed that the community dominated by S. fruticulosus was very homogeneous, and composed mainly of small maërl-forming species (S. fruticulosus and Phymatolithon calcareum).…”
Section: Methodsmentioning
confidence: 82%
“…Several ROV dives were performed in 2009 in the Menorca channel and along the Southern coast of Menorca (Barberá et al, 2009(Barberá et al, , 2012 in order to locate certain homogeneous areas harbouring the communities that characterized the seascapes found by Joher et al (2012). Three of these areas were located: one with maërl beds of S. fruticulosus, another with forests of L. rodriguezii, and a last one with P. inamoena beds.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Callionymus reticulatus inhabits coarse sand bottom, with a grain size similar to the size of the spots on the back and sides of the specimens; the species was found near Mallorca at depths of 46-68 m, significantly deeper than in the north-eastern Atlantic; Atlantic depth records based on SMNS materials range from 11-57 m. A reason for this deeper occurrence may be due to a slightly higher water temperature in the Mediterranean compared to the same depths in the north-eastern Atlantic and the presence of red algae communities such as maërl and Peyssonnelia beds which dominate the coarse sand circalittoral bottoms of the Balearic Islands down to 80 m depth (Ballesteros 1994, Ordines and Massutí 2009, Barberá et al 2012. In this sense, there seems to be a clear habitat partitioning between C. reticulatus and C. maculatus in the area sampled during the DRAGONSAL0914 survey.…”
Section: Discussionmentioning
confidence: 99%
“…Sediments composing the seafloor mainly originate from 69 local coastal erosion processes and by a variable carbonate production of bioherms 70 (Barberà et al 2012). …”
mentioning
confidence: 99%